Cdte thin film cell with multi-layered recycling composite window layer and method of making the same
By employing a multilayer cyclic composite window layer in CdTe thin-film batteries, the problems of photon transmission path optimization and pinhole phenomenon were solved, improving the conversion efficiency and stability of the batteries and achieving higher photoelectric conversion efficiency and current density.
Patent Information
- Application Number
- CN202511046318.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-29
- Publication Date
- 2025-11-28
- Estimated Expiration
- 2045-07-29
AI Technical Summary
How to optimize the photon transmission path in CdTe thin-film solar cells, avoid pinholes in the window layer, prevent short circuits and current shunting, and improve the conversion efficiency of solar cells.
A multilayer cyclic composite window layer, including metal chalcogenides with ABAB or ABCABC structures, is deposited by magnetron sputtering and forms interdiffusion between CdTe layers to avoid pinholes and promote the arrival of short-wavelength photons in the CdTe layer.
It significantly improves the photoelectric conversion efficiency of solar cells, reduces the probability of pinholes, enhances cell stability and photocurrent density, and increases cell fill factor and open-circuit voltage.
Smart Images

Figure CN120568923B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of solar cells, and relates to a CdTe thin film cell, in particular to a CdTe thin film cell with a multi-layer cyclic composite structure window layer and a preparation method thereof. BACKGROUND
[0002] Solar energy has always been a clean and environmentally friendly energy source that has attracted much attention in the market. However, the high cost of solar cells still limits their popularization and application. Therefore, further reducing the manufacturing cost is the key to the large-scale application of solar cells, and improving the photoelectric conversion efficiency of solar cells is one of the effective ways to reduce the cost. It is known that the conversion efficiency of solar cells is increased by 1%, and the cost is reduced by 7%.
[0003] CdTe (cadmium telluride) solar cell is a kind of thin film cell, which has the characteristics of simple preparation process, low cost and high efficiency. Its main material is cadmium telluride, which has excellent light absorption performance and can absorb most of the solar spectrum. The structure of CdTe solar cell usually includes glass substrate, transparent conductive layer, CdS window layer, CdTe absorption layer, back contact layer and metal electrode layer.
[0004] For the traditional CdTe thin film cell, about 7mA / cm 2 of the current is contributed by the photons with energy higher than the band gap of CdS (wavelength less than 510nm). If this part of the photons is absorbed by the CdS window layer, there will be no contribution to the current of the CdTe thin film cell, and the photons must pass through the CdS window layer to reach the CdTe absorption layer to further improve the performance of the cell. Therefore, how to reduce the loss of effective photons and improve the short-wavelength response of the cell is crucial. The traditional solution is to reduce the thickness of the CdS window layer to reduce the photoelectric current loss, but the thickness of the CdS cannot be infinitely thinned, and with the reduction of the thickness of the CdS, the VOC (open circuit voltage) and FF (fill factor) of the cell will also deteriorate simultaneously.
[0005] In addition, as the main PN junction of the CdTe thin film cell, the CdS / CdTe interface depletion region is the place of photoelectric conversion of the CdTe thin film cell, and is the core part of the whole cell. At the interface, the hexagonal structure of the CdS window layer and the cubic structure of the CdTe absorption layer have a lattice mismatch of 9.7%. Such a high lattice mismatch causes a large number of interface defects at the CdS / CdTe interface. A large number of defect energy levels are accompanied by these interface defects, which makes the photo-generated carriers trapped when transmitting at the interface, thereby seriously reducing the performance of the cell.
[0006] In order to reduce the influence of the defect level, in the heat treatment process of the battery preparation, the technicians utilize the interdiffusion characteristics between the CdS window layer and the CdTe absorption layer, so that the CdS / CdTe device forms the intermediate product CdS x Te 1-x The intermediate product can effectively reduce the large number of defect levels caused by the lattice mismatch at the interface, and the intermediate product also has the following effects on the device: (1) can passivate the CdTe surface; (2) can be used as an interface buffer layer to separate the electrical interface of CdTe and CdS from the alloy interface, thereby reducing the negative effects of the interface defect level; (3) effectively improve the carrier transport characteristics and the conversion efficiency of the battery.
[0007] However, the interdiffusion characteristics between CdS and CdTe can easily cause pinhole phenomenon of the CdS window layer. The appearance of these pinholes makes the CdTe and the TCO contact each other, forming a short circuit and current shunt of the battery, which is extremely unfavorable for large-area battery preparation.
[0008] Therefore, how to improve the structure of the CdTe thin film battery, optimize the photon transmission path while avoiding the pinhole phenomenon of the window layer, prevent the short circuit and current shunt of the battery, and improve the conversion efficiency of the solar cell, has become an urgent problem to be solved by the technical personnel in the field. SUMMARY
[0009] In view of the defects in the prior art, the purpose of the present application is to provide a CdTe thin film battery with a window layer of a multilayer cyclic composite structure and a preparation method thereof. The window layer with a multilayer cyclic composite structure optimizes the photon transmission path while avoiding the pinhole phenomenon of the window layer, prevents the short circuit and current shunt of the battery, and significantly improves the conversion efficiency of the solar cell.
[0010] To achieve this purpose, the present application adopts the following technical solutions:
[0011] In a first aspect, the present application provides a CdTe thin film battery with a window layer of a multilayer cyclic composite structure, comprising a glass substrate, a transparent conductive layer, a buffer layer, a window layer, an absorption layer, a back contact layer and a metal electrode layer arranged in layers; wherein the window layer is a multilayer cyclic composite structure, and the material of the cyclic unit comprises a metal chalcogenide compound.
[0012] The application promotes the photons with wavelength less than 510nm to pass through the window layer and reach the CdTe layer smoothly, effectively improves the performance of the battery, and the mutual diffusion between the window layer with multilayer cyclic composite structure and the CdTe layer fully avoids the pinhole phenomenon of the window layer, thereby preventing the short circuit and current shunt of the battery, and significantly improving the photoelectric conversion efficiency of the solar cell.
[0013] Preferably, the multilayer cyclic composite structure comprises an ABAB structure or an ABCABC structure, wherein A, B and C respectively represent different metal chalcogenides.
[0014] Preferably, the metal chalcogenide comprises any one or a combination of at least two of CdS, CdSe, ZnS or ZnSe.
[0015] Preferably, the metal chalcogenide is doped with any one or a combination of at least two of oxygen, nitrogen or chlorine.
[0016] Preferably, the content of the doping element in the metal chalcogenide is ≤32wt%.
[0017] Preferably, the single-layer thickness of the window layer is 10-50nm.
[0018] Preferably, the total thickness of the window layer is 10-500nm.
[0019] In the second aspect, the application provides a preparation method of the CdTe thin film battery with the window layer of multilayer cyclic composite structure as described in the first aspect, and the preparation method comprises the following steps:
[0020] (1) depositing a transparent conductive layer and a buffer layer on the surface of a glass substrate in sequence;
[0021] (2) depositing a window layer with multilayer cyclic composite structure on the surface of the buffer layer;
[0022] (3) depositing an absorption layer, a back contact layer and a metal electrode layer on the surface of the window layer in sequence, and obtaining the CdTe thin film battery with the window layer of multilayer cyclic composite structure after annealing treatment.
[0023] Preferably, the glass substrate in step (1) comprises soda-lime glass.
[0024] Preferably, the deposition method of the transparent conductive layer and the buffer layer in step (1) comprises chemical vapor deposition method independently.
[0025] Preferably, the material of the transparent conductive layer in step (1) comprises fluorine-doped tin oxide.
[0026] Preferably, the material of the buffer layer in step (1) comprises any one of tin oxide, zinc tin oxide or cadmium tin oxide.
[0027] Preferably, the deposition method of the window layer in step (2) comprises a magnetron sputtering method.
[0028] Preferably, the gas atmosphere of the magnetron sputtering method is argon or a combination of argon and a doping gas, and the doping gas comprises any one or a combination of at least two of oxygen, nitrogen and chlorine.
[0029] Preferably, the vacuum degree of the magnetron sputtering method is 1-10 mTorr, and the power density is 0.1-5 W / cm 2 .
[0030] Preferably, the deposition method of the absorbing layer in step (3) comprises a near-space sublimation method, and the deposition temperature is 400-800℃.
[0031] Preferably, the deposition method of the back contact layer and the metal electrode layer in step (3) independently comprises a magnetron sputtering method.
[0032] Preferably, the material of the absorbing layer in step (3) comprises cadmium telluride, and the thickness is 2-6 μm.
[0033] Preferably, the material of the back contact layer in step (3) comprises copper-doped zinc telluride.
[0034] Preferably, the material of the metal electrode layer in step (3) comprises molybdenum.
[0035] Preferably, the temperature of the annealing treatment in step (3) is 100-300℃.
[0036] Preferably, the time of the annealing treatment in step (3) is 1-60 min.
[0037] Compared with the prior art, the present application has the following beneficial effects:
[0038] The present application promotes the photons with a wavelength less than 510 nm to pass through the window layer and reach the CdTe layer smoothly, effectively improves the battery performance, and the mutual diffusion between the window layer with the multi-layer cyclic composite structure and the CdTe layer fully avoids the pinhole phenomenon of the window layer, thereby preventing the short circuit and current shunt of the battery, and significantly improving the photoelectric conversion efficiency of the solar cell. BRIEF DESCRIPTION OF DRAWINGS
[0039] Figure 1 is a schematic diagram of the CdTe thin film battery structure provided in Examples 1-4;
[0040] Figure 2is a schematic diagram of a CdTe thin film battery structure provided by Comparative Example 1.
[0041] wherein: 10-glass substrate; 20-transparent conductive layer; 30-buffer layer; 40-window layer; 41-CdS layer; 42-CdSe layer; 50-absorbing layer; 60-back contact layer; 70-metal electrode layer. DETAILED DESCRIPTION
[0042] The technical solutions of the present application will be further illustrated by specific embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present application and should not be regarded as specific limitations of the present application.
[0043] Some embodiments of the present application provide a CdTe thin film battery with a window layer of a multi-layer cyclic composite structure, comprising a glass substrate, a transparent conductive layer, a buffer layer, a window layer, an absorbing layer, a back contact layer and a metal electrode layer arranged in layers; wherein the window layer is a multi-layer cyclic composite structure, and the material of the cyclic unit includes a metal chalcogenide compound.
[0044] The present application sets a window layer of a multi-layer cyclic composite structure in the CdTe thin film battery, which promotes the photons with a wavelength less than 510 nm to pass through the window layer and reach the CdTe layer smoothly, effectively improves the battery performance, and the mutual diffusion between the window layer of the multi-layer cyclic composite structure and the CdTe layer fully avoids the pinhole phenomenon of the window layer, thereby preventing the short circuit and current shunt of the battery, and significantly improving the photoelectric conversion efficiency of the solar cell.
[0045] Specifically, for photons with a wavelength less than 510 nm, under the traditional single window layer structure, part of the photons are difficult to reach the CdTe layer smoothly due to absorption, scattering and other reasons. The multi-layer cyclic composite structure window layer defined in the present application has special optical and physical properties, which can optimize the photon transmission path, reduce the loss of photons in the window layer, make them pass through the layer more efficiently, and finally reach the CdTe layer smoothly, resulting in an increase in the number of photons entering the CdTe layer, thereby effectively exciting more photo-generated carriers, improving the photo-generated current of the battery, and finally significantly improving the overall performance and photoelectric conversion efficiency of the battery.
[0046] For example, assuming that the CdTe thin film battery with a traditional single-layer CdS window layer has a transmittance of 60% for photons with a wavelength less than 510 nm, which means that 40% of the photons in this wavelength band cannot be effectively utilized. In contrast, after the present application adopts a window layer of a multi-layer cyclic composite structure, the transmittance can be improved to 80%, significantly increasing the number of available photons; accordingly, the short-circuit current density of the thin film battery can be improved from 25 mA / cm² to 30 mA / cm², and the photoelectric conversion efficiency will also be significantly improved.
[0047] In addition, in the interdiffusion process between the window layer and the CdTe layer, the single window layer is prone to pinhole phenomenon because its structure and material properties are difficult to maintain uniform and complete under the influence of long-term interdiffusion and process. Once a pinhole occurs, CdTe will be in direct contact with the transparent conductive oxide, like a "short circuit channel" that should not exist in the circuit, causing internal current to shunt, and the current that should flow along the normal path and output work externally is dispersed. In severe cases, it can even directly cause the battery to short circuit and cannot normally output power. Especially when preparing a large-area battery, the probability of pinhole occurrence is relatively higher due to the increase in area, and the impact on battery performance is more prominent, which can greatly reduce the yield and stability of the battery.
[0048] To this end, the multi-layer cyclic composite structure window layer provided by the present application can effectively fill the position where a pinhole may occur and avoid the generation of pinholes from the root cause by virtue of its unique structure design and material composition, better filling and compatibility, etc. in the interdiffusion process with CdTe. For example, in actual battery production monitoring, the probability of pinhole occurrence in a large-area cadmium telluride solar cell using a multi-layer cyclic composite structure window layer can be reduced by more than 80% compared to a battery with a traditional structure, greatly reducing the occurrence of battery short circuit and current shunt, ensuring the stability of the battery during large-area preparation and actual use, and enabling the fill factor of the battery to be maintained at a high level, thereby ensuring a high photoelectric conversion efficiency.
[0049] In some embodiments, the multi-layer cyclic composite structure includes an ABAB structure or an ABCABC structure, where A, B, and C respectively represent different metal chalcogenides.
[0050] In some embodiments, the metal chalcogenide includes any one or a combination of at least two of CdS, CdSe, ZnS, or ZnSe, and a typical but non-limiting combination includes a combination of CdS and CdSe, or a combination of ZnS and ZnSe.
[0051] In some embodiments, the metal chalcogenide is doped with any one or a combination of at least two of oxygen, nitrogen, or chlorine, and a typical but non-limiting combination includes a combination of oxygen and nitrogen, a combination of nitrogen and chlorine, a combination of oxygen and chlorine, or a combination of oxygen, nitrogen, and chlorine.
[0052] In some embodiments, the content of the doping element in the metal chalcogenide compound is ≤32wt%, for example, it can be 2wt%, 4wt%, 6wt%, 8wt%, 10wt%, 12wt%, 14wt%, 16wt%, 18wt%, 20wt%, 22wt%, 24wt%, 26wt%, 28wt%, 30wt% or 32wt%, but not limited to the listed values, and other values not listed in the range are also applicable.
[0053] In the present application, the defect energy level bands of the CdS / CdTe interface have a great negative impact on the performance of the battery. These defect energy level bands are like a "trap" that can capture photo-generated carriers, so that the photo-generated carriers are recombined before they effectively participate in conduction and output electricity, resulting in a decrease in the number of effective carriers available to form current, thereby reducing the photoelectric conversion efficiency of the battery. To this end, the present application can precisely introduce specific doping elements into the window layer of the multilayer cyclic composite structure and achieve a specific composition distribution, thereby finely regulating the atomic arrangement, energy level structure and the like at the interface, "filling" the defect energy level bands, reducing the defect state density at the interface, and allowing the photo-generated carriers to be more smoothly transported and separated at the interface, thereby improving the collection efficiency of the carriers.
[0054] In some embodiments, the thickness of a single layer of the window layer is 10-50nm, for example, it can be 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm or 50nm, but not limited to the listed values, and other values not listed in the range are also applicable.
[0055] In some embodiments, the total thickness of the window layer is 10-500nm, for example, it can be 10nm, 50nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm or 500nm, but not limited to the listed values, and other values not listed in the range are also applicable.
[0056] Some embodiments of the present application also provide a preparation method of a CdTe thin film battery with a window layer of a multilayer cyclic composite structure according to any one of the above embodiments, which comprises the following steps:
[0057] (1) depositing a transparent conductive layer and a buffer layer on the surface of a glass substrate in sequence;
[0058] (2) depositing a window layer of a multilayer cyclic composite structure on the surface of the buffer layer;
[0059] (3) depositing an absorption layer, a back contact layer and a metal electrode layer on the surface of the window layer in sequence, and obtaining a CdTe thin film cell with a multi-layer cyclic composite structure window layer after annealing treatment.
[0060] In some embodiments, the glass substrate of step (1) comprises soda lime glass.
[0061] In some embodiments, the deposition method of the transparent conductive layer and the buffer layer of step (1) independently comprises chemical vapor deposition.
[0062] In some embodiments, the material of the transparent conductive layer of step (1) comprises fluorine-doped tin oxide.
[0063] In some embodiments, the material of the buffer layer of step (1) comprises any one of tin oxide, zinc tin oxide or cadmium tin oxide.
[0064] In some embodiments, the deposition method of the window layer of step (2) comprises magnetron sputtering.
[0065] In some embodiments, the gas atmosphere of the magnetron sputtering comprises argon, or a combination of argon and a doping gas, and the doping gas comprises any one or a combination of at least two of oxygen, nitrogen and chlorine, and typical but non-limiting combinations include a combination of oxygen and nitrogen, a combination of nitrogen and chlorine, a combination of oxygen and chlorine, or a combination of oxygen, nitrogen and chlorine.
[0066] In some embodiments, the vacuum degree of the magnetron sputtering is 1-10 mTorr, for example, it can be 1 mTorr, 2 mTorr, 3 mTorr, 4 mTorr, 5 mTorr, 6 mTorr, 7 mTorr, 8 mTorr, 9 mTorr or 10 mTorr, and the power density is 0.1-5 W / cm 2 , for example, it can be 0.1 W / cm 2 , 0.5 W / cm 2 , 1 W / cm 2 , 1.5 W / cm 2 , 2 W / cm 2 , 2.5 W / cm 2 , 3 W / cm 2 , 3.5 W / cm 2 , 4 W / cm 2 , 4.5 W / cm 2 or 5 W / cm 2 , but not limited to the listed values, and other unlisted values within the range are also applicable.
[0067] In some embodiments, the deposition method of the absorbing layer in step (3) comprises a near-space sublimation method, and the deposition temperature is 400-800 °C, for example, it can be 400 °C, 450 °C, 500 °C, 550 °C, 600 °C, 650 °C, 700 °C, 750 °C or 800 °C, but not only limited to the listed values, other values not listed in this range are also applicable.
[0068] In some embodiments, the deposition method of the back contact layer and the metal electrode layer in step (3) comprises a magnetron sputtering method, respectively.
[0069] In some embodiments, the material of the absorbing layer in step (3) comprises cadmium telluride, and the thickness is 2-6 μm, for example, it can be 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm or 6 μm, but not only limited to the listed values, other values not listed in this range are also applicable.
[0070] In some embodiments, the material of the back contact layer in step (3) comprises copper-doped zinc telluride.
[0071] In some embodiments, the material of the metal electrode layer in step (3) comprises molybdenum.
[0072] In some embodiments, the annealing temperature in step (3) is 100-300 °C, for example, it can be 100 °C, 120 °C, 140 °C, 160 °C, 180 °C, 200 °C, 220 °C, 240 °C, 260 °C, 280 °C or 300 °C, but not only limited to the listed values, other values not listed in this range are also applicable.
[0073] In some embodiments, the annealing time in step (3) is 1-60 min, for example, it can be 1 min, 5 min, 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min or 60 min, but not only limited to the listed values, other values not listed in this range are also applicable.
[0074] The CdTe thin film battery provided by the application can diffuse, react and synergize with the CdTe absorption layer according to the set composition distribution of the doped elements in the multi-layer cyclic composite structure window layer after annealing, so that a specific PN junction with excellent characteristics is formed. The specific PN junction has just the right degree of band bending and a stable and suitable built-in electric field. The built-in electric field acts as a "pusher" to effectively separate the photo-generated carriers in the PN junction region, with electrons moving to the N region and holes moving to the P region, and then being conducted out through the electrodes to form a current. In addition, the suitable band bending helps the directional movement of the carriers and reduces the reverse recombination and the like, thereby improving the open-circuit voltage and short-circuit current of the battery, and finally achieving a significant improvement in the photoelectric conversion efficiency.
[0075] Exemplarily, in the related experimental tests, after the multi-layer cyclic composite structure window layer is used in the CdTe thin film battery, the CdS / CdTe interface defect state density of the thin film battery can be reduced by 30%-40% compared with that of the traditional battery, the open-circuit voltage can be increased from 0.8V to about 0.92V, the short-circuit current density can be increased from 25mA / cm² to 30mA / cm², and the photoelectric conversion efficiency can also be increased from about 15% to 20% and above.
[0076] As can be seen, the application breaks through the bottleneck of the single-layer CdS window layer for improving the efficiency of the thin film solar cell by developing the multi-layer cyclic composite structure window layer, which plays a crucial role in further improving the photoelectric conversion efficiency of the cadmium telluride solar cell, and has significant advantages in improving the photon utilization rate, ensuring the stability of the battery structure, optimizing the interface characteristics and the like.
[0077] The numerical range described in the application includes not only the point values listed above, but also any point values between the above numerical ranges that are not listed, and the specific point values included in the range are not listed due to the length and the consideration of simplicity.
[0078] Embodiment 1
[0079] The embodiment provides a CdTe thin film battery with a multi-layer cyclic composite structure window layer, as shown in the figure, the CdTe thin film battery comprises a glass substrate 10, a transparent conductive layer 20, a buffer layer 30, a window layer 40, an absorption layer 50, a back contact layer 60 and a metal electrode layer 70 which are stacked. Figure 1 The window layer 40 is a multi-layer cyclic composite structure, specifically an ABAB structure, A refers to a CdS layer 41, and B refers to a CdSe layer 42, and the CdS layer 41 and the CdSe layer 42 close to the buffer layer 30 are both doped with oxygen elements, and the doping content is 20wt%; the total thickness of the window layer 40 is 120nm.
[0080] In this embodiment, the glass substrate 10 is soda-lime glass; the transparent conductive layer 20 is fluorine-doped tin oxide (FTO); the buffer layer 30 is tin oxide (SnO); the absorption layer 50 is cadmium telluride (CdTe); the back contact layer 60 is copper-doped zinc telluride (ZnTe:Cu); and the metal electrode layer 70 is molybdenum (Mo).
[0081] In this embodiment, the method for preparing the CdTe thin-film cell includes the following steps:
[0082] (1) The transparent conductive layer 20 and the buffer layer 30 are sequentially deposited on the surface of the glass substrate 10 by chemical vapor deposition;
[0083] (2) The window layer 40 with a multilayer cyclic composite structure is deposited on the surface of the buffer layer 30 by magnetron sputtering, specifically including:
[0084] (2.1) In an Ar and O2 mixed gas atmosphere, the vacuum degree of the sputtering environment is controlled to be 5 mTorr, and the power density is controlled to be 2.5 W / cm2, and a CdS layer 41 with a thickness of 20 nm is deposited on the surface of the buffer layer 30 as a first window sublayer; 2
[0085] (2.2) In an Ar and O2 mixed gas atmosphere, the vacuum degree of the sputtering environment is controlled to be 5 mTorr, and the power density is controlled to be 2.5 W / cm2, and a CdSe layer 42 with a thickness of 30 nm is deposited on the surface of the first window sublayer as a second window sublayer; 2
[0086] (2.3) In an Ar gas atmosphere, the vacuum degree of the sputtering environment is controlled to be 5 mTorr, and the power density is controlled to be 2.5 W / cm2, and a CdS layer 41 with a thickness of 20 nm is deposited on the surface of the second window sublayer as a third window sublayer; 2
[0087] (2.4) In an Ar gas atmosphere, the vacuum degree of the sputtering environment is controlled to be 5 mTorr, and the power density is controlled to be 2.5 W / cm2, and a CdSe layer 42 with a thickness of 50 nm is deposited on the surface of the third window sublayer as a fourth window sublayer; 2
[0088] (3) CdTe is deposited on the surface of the window layer 40 by near-space sublimation, the deposition temperature is controlled to be 700°C, and an absorption layer 50 with a thickness of 5 μm is obtained; then cadmium chloride solution is sprayed on the surface of the absorption layer 50 and annealed at 400°C;
[0089] (4) In an Ar gas atmosphere, ZnTe:Cu is magnetron sputtered on the surface of the absorption layer 50 to obtain a back contact layer 60;
[0090] (5) In an Ar gas atmosphere, Mo is magnetron sputtered on the surface of the back contact layer 60 to obtain a metal electrode layer 70;
[0091] (6) Anneal the battery cell, control the annealing temperature to 200°C and the annealing time to 30 min, and obtain the CdTe thin film battery.
[0092] In this embodiment, the specific conditions of the chemical vapor deposition method in step (1), the near-space sublimation method in step (3), and the magnetron sputtering in steps (4) and (5) have no significant impact on the photoelectric conversion performance of the obtained CdTe thin film battery, so their specific process parameters are not specifically described here.
[0093] Example 2
[0094] This embodiment provides a CdTe thin-film battery with a multilayer cyclic composite structure window layer, such as... Figure 1 As shown, the CdTe thin-film battery includes a glass substrate 10, a transparent conductive layer 20, a buffer layer 30, a window layer 40, an absorber layer 50, a back contact layer 60, and a metal electrode layer 70, all stacked together. The window layer 40 has a multilayer cyclic composite structure, specifically an ABAB structure, where A represents a CdS layer 41 and B represents a CdSe layer 42. Both the CdS layer 41 and the CdSe layer 42 near the buffer layer 30 are doped with nitrogen at a doping content of 25 wt%. The total thickness of the window layer 40 is 120 nm.
[0095] In this embodiment, the glass substrate 10 is soda-lime glass; the transparent conductive layer 20 is made of fluorine-doped tin oxide (FTO); the buffer layer 30 is made of tin oxide (SnO); the absorption layer 50 is made of cadmium telluride (CdTe); the back contact layer 60 is made of copper-doped zinc telluride (ZnTe:Cu); and the metal electrode layer 70 is made of molybdenum (Mo).
[0096] In this embodiment, the preparation method of the above-mentioned CdTe thin film battery includes the following steps:
[0097] (1) A transparent conductive layer 20 and a buffer layer 30 are sequentially deposited on the surface of a glass substrate 10 by chemical vapor deposition.
[0098] (2) A multilayer cyclic composite window layer 40 is deposited on the surface of the buffer layer 30 using magnetron sputtering, specifically including:
[0099] (2.1) In a mixed gas atmosphere of Ar and N2, the vacuum level of the sputtering environment is controlled at 5 mTorr and the power density is 2.5 W / cm³. 2a CdS layer 41 with a thickness of 20 nm is deposited on the surface of the buffer layer 30 as a first window sub-layer;
[0100] (2.2) In a mixed gas atmosphere of Ar and N2, the vacuum degree of the sputtering environment is controlled to be 5 mTorr, and the power density is controlled to be 2.5 W / cm 2 a CdSe layer 42 with a thickness of 30 nm is deposited on the surface of the first window sub-layer as a second window sub-layer;
[0101] (2.3) In an Ar gas atmosphere, the vacuum degree of the sputtering environment is controlled to be 5 mTorr, and the power density is controlled to be 2.5 W / cm 2 a CdS layer 41 with a thickness of 20 nm is deposited on the surface of the second window sub-layer as a third window sub-layer;
[0102] (2.4) In an Ar gas atmosphere, the vacuum degree of the sputtering environment is controlled to be 5 mTorr, and the power density is controlled to be 2.5 W / cm 2 a CdSe layer 42 with a thickness of 50 nm is deposited on the surface of the third window sub-layer as a fourth window sub-layer;
[0103] (3) A CdTe is deposited on the surface of the window layer 40 by a near-space sublimation method, and the deposition temperature is controlled to be 700 ℃, so as to obtain an absorption layer 50 with a thickness of 5 μm; then a cadmium chloride solution is sprayed on the surface of the absorption layer 50 and is subjected to an annealing treatment at 400 ℃;
[0104] (4) In an Ar gas atmosphere, a ZnTe:Cu is magnetron sputtered on the surface of the absorption layer 50, so as to obtain a back contact layer 60;
[0105] (5) In an Ar gas atmosphere, a Mo is magnetron sputtered on the surface of the back contact layer 60, so as to obtain a metal electrode layer 70;
[0106] (6) The cell piece is subjected to an annealing treatment, the annealing temperature is controlled to be 200 ℃, and the annealing time is controlled to be 30 min, so as to obtain the CdTe thin-film cell.
[0107] In the embodiment, the specific conditions of the chemical vapor deposition method in step (1), the near-space sublimation method in step (3), and the magnetron sputtering in steps (4) and (5) have no obvious influence on the photoelectric conversion performance of the obtained CdTe thin-film cell, and therefore the specific process parameters are not particularly described herein.
[0108] Embodiment 3
[0109] The embodiment provides a CdTe thin-film cell with a window layer of a multi-layer cyclic composite structure, as shown in Figure 1As shown, the CdTe thin film battery includes a glass substrate 10, a transparent conductive layer 20, a buffer layer 30, a window layer 40, an absorption layer 50, a back contact layer 60 and a metal electrode layer 70 arranged in a stack. The window layer 40 is a multilayer cyclic composite structure, specifically an ABAB structure, A refers to a CdS layer 41, and B refers to a CdSe layer 42, and the CdS layer 41 and the CdSe layer 42 close to the buffer layer 30 are both doped with oxygen and nitrogen elements, and the doping content is 10wt%; the total thickness of the window layer 40 is 120nm.
[0110] In this embodiment, the glass substrate 10 is soda-lime glass; the material of the transparent conductive layer 20 is fluorine-doped tin oxide (FTO); the material of the buffer layer 30 is tin oxide (SnO); the material of the absorption layer 50 is cadmium telluride (CdTe); the material of the back contact layer 60 is copper-doped zinc telluride (ZnTe:Cu); and the material of the metal electrode layer 70 is molybdenum (Mo).
[0111] In this embodiment, the preparation method of the CdTe thin film battery includes the following steps:
[0112] (1) The transparent conductive layer 20 and the buffer layer 30 are sequentially deposited on the surface of the glass substrate 10 by chemical vapor deposition;
[0113] (2) The window layer 40 of a multilayer cyclic composite structure is deposited on the surface of the buffer layer 30 by magnetron sputtering, specifically including:
[0114] (2.1) In an Ar, O2 and N2 mixed gas atmosphere, the vacuum degree of the sputtering environment is controlled to be 5mTorr, and the power density is 2.5W / cm 2 A CdS layer 41 with a thickness of 20nm is deposited on the surface of the buffer layer 30 as a first window sublayer;
[0115] (2.2) In an Ar, O2 and N2 mixed gas atmosphere, the vacuum degree of the sputtering environment is controlled to be 5mTorr, and the power density is 2.5W / cm 2 A CdSe layer 42 with a thickness of 30nm is deposited on the surface of the first window sublayer as a second window sublayer;
[0116] (2.3) In an Ar gas atmosphere, the vacuum degree of the sputtering environment is controlled to be 5mTorr, and the power density is 2.5W / cm 2 A CdS layer 41 with a thickness of 20nm is deposited on the surface of the second window sublayer as a third window sublayer;
[0117] (2.4) In an Ar gas atmosphere, the vacuum degree of the sputtering environment is controlled to be 5mTorr, and the power density is 2.5W / cm 2a CdSe layer 42 with a thickness of 50 nm is deposited on the surface of the third window sub-layer as a fourth window sub-layer;
[0118] (3) CdTe is deposited on the surface of the window layer 40 by using a close space sublimation method, and a deposition temperature is controlled at 700°C to obtain an absorption layer 50 with a thickness of 5 μm; then, a cadmium chloride solution is sprayed on the surface of the absorption layer 50 and is subjected to an annealing treatment at 400°C;
[0119] (4) ZnTe:Cu is magnetron sputtered on the surface of the absorption layer 50 in an Ar gas atmosphere to obtain a back contact layer 60;
[0120] (5) Mo is magnetron sputtered on the surface of the back contact layer 60 in an Ar gas atmosphere to obtain a metal electrode layer 70;
[0121] (6) The cell is subjected to an annealing treatment, and an annealing temperature is controlled at 200°C and an annealing time is controlled at 30 min to obtain the CdTe thin film cell.
[0122] In the embodiment, the specific conditions of the chemical vapor deposition method in step (1), the close space sublimation method in step (3), and the magnetron sputtering in steps (4) and (5) have no obvious influence on the photoelectric conversion performance of the obtained CdTe thin film cell, and therefore, the specific process parameters are not particularly described herein.
[0123] Embodiment 4
[0124] The embodiment provides a CdTe thin film cell with a window layer of a multilayer cyclic composite structure, as shown in the accompanying drawings. Figure 1 The CdTe thin film cell includes a glass substrate 10, a transparent conductive layer 20, a buffer layer 30, a window layer 40, an absorption layer 50, a back contact layer 60, and a metal electrode layer 70 which are arranged in layers. The window layer 40 is of a multilayer cyclic composite structure, specifically, an ABAB structure, A refers to a CdS layer 41, and B refers to a CdSe layer 42. The total thickness of the window layer 40 is 120 nm.
[0125] In the embodiment, the glass substrate 10 is a soda-lime glass; the transparent conductive layer 20 is made of fluorine-doped tin oxide (FTO); the buffer layer 30 is made of tin oxide (SnO); the absorption layer 50 is made of cadmium telluride (CdTe); the back contact layer 60 is made of copper-doped zinc telluride (ZnTe:Cu); and the metal electrode layer 70 is made of molybdenum (Mo).
[0126] In the embodiment, the preparation method of the CdTe thin film cell includes the following steps:
[0127] (1) Depositing transparent conductive layer 20 and buffer layer 30 on the surface of glass substrate 10 in sequence by chemical vapor deposition method;
[0128] (2) Depositing window layer 40 with multilayer cyclic composite structure on the surface of buffer layer 30 by magnetron sputtering method, specifically including:
[0129] (2.1) Depositing CdS layer 41 with a thickness of 20 nm as a first window sub-layer on the surface of buffer layer 30 in an Ar gas atmosphere, controlling the vacuum degree of the sputtering environment to be 5 mTorr and the power density to be 2.5 W / cm 2
[0130] (2.2) Depositing CdSe layer 42 with a thickness of 30 nm as a second window sub-layer on the surface of the first window sub-layer in an Ar gas atmosphere, controlling the vacuum degree of the sputtering environment to be 5 mTorr and the power density to be 2.5 W / cm 2
[0131] (2.3) Depositing CdS layer 41 with a thickness of 20 nm as a third window sub-layer on the surface of the second window sub-layer in an Ar gas atmosphere, controlling the vacuum degree of the sputtering environment to be 5 mTorr and the power density to be 2.5 W / cm 2
[0132] (2.4) Depositing CdSe layer 42 with a thickness of 50 nm as a fourth window sub-layer on the surface of the third window sub-layer in an Ar gas atmosphere, controlling the vacuum degree of the sputtering environment to be 5 mTorr and the power density to be 2.5 W / cm 2
[0133] (3) Depositing CdTe on the surface of window layer 40 by near-space sublimation method, controlling the deposition temperature to be 700℃, obtaining an absorption layer 50 with a thickness of 5 μm; then spraying a cadmium chloride solution on the surface of absorption layer 50 and performing 400℃ annealing treatment;
[0134] (4) Magnetron sputtering ZnTe:Cu on the surface of absorption layer 50 in an Ar gas atmosphere, obtaining a back contact layer 60;
[0135] (5) Magnetron sputtering Mo on the surface of back contact layer 60 in an Ar gas atmosphere, obtaining a metal electrode layer 70;
[0136] (6) Annealing treatment is performed on the cell sheet, controlling the annealing temperature to be 200℃ and the annealing time to be 30 min, obtaining the CdTe thin film cell.
[0137] The specific conditions of the chemical vapor deposition method in step (1), the near-space sublimation method in step (3), and the magnetron sputtering in steps (4) and (5) have no obvious influence on the photoelectric conversion performance of the obtained CdTe thin film battery, and therefore, the specific process parameters are not particularly described herein.
[0138] Embodiment 5
[0139] The embodiment provides a CdTe thin film battery with a window layer of a multilayer cyclic composite structure, which comprises a glass substrate 10, a transparent conductive layer 20, a buffer layer 30, a window layer 40, an absorption layer 50, a back contact layer 60, and a metal electrode layer 70 which are arranged in layers. The window layer 40 is a multilayer cyclic composite structure, specifically, a layer stack of a CdS layer 41 doped with oxygen elements, a CdS layer 41 not doped with oxygen elements, a CdSe layer 42 doped with oxygen elements, a CdS layer 41 not doped with oxygen elements, and a CdSe layer 42 not doped with oxygen elements, and the content of oxygen elements doped in each layer is 20wt%; and the total thickness of the window layer 40 is 130nm.
[0140] In the embodiment, the glass substrate 10 is soda-lime glass; the material of the transparent conductive layer 20 is fluorine-doped tin oxide (FTO); the material of the buffer layer 30 is tin oxide (SnO); the material of the absorption layer 50 is cadmium telluride (CdTe); the material of the back contact layer 60 is copper-doped zinc telluride (ZnTe:Cu); and the material of the metal electrode layer 70 is molybdenum (Mo).
[0141] The preparation method of the CdTe thin film battery in the embodiment comprises the following steps:
[0142] (1) a transparent conductive layer 20 and a buffer layer 30 are sequentially deposited on the surface of the glass substrate 10 by a chemical vapor deposition method;
[0143] (2) a window layer 40 of a multilayer cyclic composite structure is deposited on the surface of the buffer layer 30 by a magnetron sputtering method, specifically comprising:
[0144] (2.1) in an Ar and O2 mixed gas atmosphere, the vacuum degree of the sputtering environment is controlled to be 5mTorr, and the power density is controlled to be 2.5W / cm 2 a CdS layer 41 with a thickness of 10nm is deposited on the surface of the buffer layer 30 as a first window sublayer;
[0145] (2.2) in an Ar gas atmosphere, the vacuum degree of the sputtering environment is controlled to be 5mTorr, and the power density is controlled to be 2.5W / cm 2 a CdS layer 41 with a thickness of 20nm is deposited on the surface of the first window sublayer as a second window sublayer;
[0146] (2.3) In the mixed gas atmosphere of Ar and O2, the vacuum degree of the sputtering environment is controlled to be 5 mTorr, and the power density is 2.5 W / cm 2 A CdSe layer 42 with a thickness of 30 nm is deposited on the surface of the second window sub-layer as a third window sub-layer;
[0147] (2.4) In the gas atmosphere of Ar, the vacuum degree of the sputtering environment is controlled to be 5 mTorr, and the power density is 2.5 W / cm 2 A CdS layer 41 with a thickness of 20 nm is deposited on the surface of the third window sub-layer as a fourth window sub-layer;
[0148] (2.5) In the gas atmosphere of Ar, the vacuum degree of the sputtering environment is controlled to be 5 mTorr, and the power density is 2.5 W / cm 2 A CdSe layer 42 with a thickness of 50 nm is deposited on the surface of the fourth window sub-layer as a fifth window sub-layer;
[0149] (3) A CdTe is deposited on the surface of the window layer 40 by a close space sublimation method, and the deposition temperature is controlled to be 700 ℃, so as to obtain an absorption layer 50 with a thickness of 5 μm; then a cadmium chloride solution is sprayed on the surface of the absorption layer 50 and is subjected to an annealing treatment at 400 ℃;
[0150] (4) A ZnTe:Cu is magnetron sputtered on the surface of the absorption layer 50 in the gas atmosphere of Ar, so as to obtain a back contact layer 60;
[0151] (5) A Mo is magnetron sputtered on the surface of the back contact layer 60 in the gas atmosphere of Ar, so as to obtain a metal electrode layer 70;
[0152] (6) The cell piece is subjected to an annealing treatment, the annealing temperature is controlled to be 200 ℃, and the annealing time is 30 min, so as to obtain the CdTe thin film cell.
[0153] In the embodiment, the specific conditions of the chemical vapor deposition method in step (1), the close space sublimation method in step (3), and the magnetron sputtering in steps (4) and (5) have no obvious influence on the photoelectric conversion performance of the obtained CdTe thin film cell, and therefore the specific process parameters are not particularly described herein.
[0154] Comparative Example 1
[0155] The present comparative example provides a CdTe thin film cell, as shown in the following structural formula: Figure 2 The CdTe thin film cell includes a glass substrate 10, a transparent conductive layer 20, a buffer layer 30, a window layer 40, an absorption layer 50, a back contact layer 60, and a metal electrode layer 70 which are arranged in layers.
[0156] In the comparative example, the glass substrate 10 is soda-lime glass; the transparent conductive layer 20 is fluorine-doped tin oxide (FTO); the buffer layer 30 is tin oxide (SnO); the window layer 40 is cadmium sulfide (CdS); the absorption layer 50 is cadmium telluride (CdTe); the back contact layer 60 is copper-doped zinc telluride (ZnTe:Cu); and the metal electrode layer 70 is molybdenum (Mo).
[0157] In the comparative example, the preparation method of the CdTe thin film cell includes the following steps:
[0158] (1) The transparent conductive layer 20 and the buffer layer 30 are sequentially deposited on the surface of the glass substrate 10 by chemical vapor deposition;
[0159] (2) In an Ar gas atmosphere, the vacuum degree of the sputtering environment is controlled to be 5 mTorr, and the power density is controlled to be 2.5 W / cm 2 A CdS layer with a thickness of 150 nm is deposited on the surface of the buffer layer 30 as the window layer 40;
[0160] (3) CdTe is deposited on the surface of the window layer 40 by near-space sublimation, the deposition temperature is controlled to be 700°C, and an absorption layer 50 with a thickness of 5 μm is obtained; then a cadmium chloride solution is sprayed on the surface of the absorption layer 50 and annealed at 400°C;
[0161] (4) In an Ar gas atmosphere, ZnTe:Cu is magnetron sputtered on the surface of the absorption layer 50 to obtain the back contact layer 60;
[0162] (5) In an Ar gas atmosphere, Mo is magnetron sputtered on the surface of the back contact layer 60 to obtain the metal electrode layer 70;
[0163] (6) The cell is annealed, the annealing temperature is controlled to be 200°C, and the annealing time is controlled to be 30 min to obtain the CdTe thin film cell.
[0164] In the comparative example, the specific conditions of the chemical vapor deposition method in step (1), the near-space sublimation method in step (3), and the magnetron sputtering in steps (4) and (5) have no obvious effect on the photoelectric conversion performance of the obtained CdTe thin film cell, so the specific process parameters are not particularly mentioned here.
[0165] Performance test
[0166] The conversion efficiency, fill factor, short-circuit current, and open-circuit voltage of the CdTe thin film cells obtained in Examples 1-5 and Comparative Example 1 are tested, and the standard test conditions are used: the total irradiance is specified to be 1000 W / m 2, the spectrum adopts the standard sunlight spectrum of AM1.5 total irradiance, the test temperature is 25℃, and the allowable error range is: 25±1℃ (for reference, IEC60904 or ASTM G173-03 Global).
[0167] The relevant test results are shown in Table 1 below.
[0168] Table 1
[0169]
[0170] As can be seen from Table 1, compared with Comparative Example 1, Example 4 optimizes the window layer structure, thereby realizing all-round improvement of open-circuit voltage, short-circuit current, fill factor and conversion efficiency; Examples 1-3 further improve the open-circuit voltage, short-circuit current, fill factor and conversion efficiency by optimizing the window layer structure and doping different elements; Examples 1 and 5 further improve the open-circuit voltage, short-circuit current, fill factor and conversion efficiency by optimizing the window layer structure and specially doping oxygen elements.
[0171] It can be seen that, by arranging the window layer with the multilayer cyclic composite structure in the CdTe thin film battery, the present application promotes the photons with wavelength less than 510nm to pass through the window layer and reach the CdTe layer smoothly, effectively improves the battery performance, and the mutual diffusion effect between the window layer with the multilayer cyclic composite structure and the CdTe layer fully avoids the pinhole phenomenon of the window layer, thereby preventing the battery short circuit and current shunt, and significantly improving the photoelectric conversion efficiency of the solar cell.
[0172] The above merely describes the specific embodiments of the present application, but the protection scope of the present application is not limited thereto. It should be understood by those skilled in the art that any changes or replacements within the technical scope disclosed by the present application can be easily conceived by those skilled in the art, and all such changes or replacements fall within the protection scope and disclosure scope of the present application.
Claims
1. A CdTe thin film cell having a multi-layered cycle composite window layer, comprising a glass substrate, a transparent conductive layer, a buffer layer, a window layer, an absorber layer, a back contact layer and a metal electrode layer, which are stacked, characterized in that, The window layer is a multi-layer cyclic composite structure, and the material of the cyclic unit comprises a metal chalcogenide; The multi-layer cyclic composite structure comprises an ABAB structure or an ABCABC structure, wherein A, B, and C respectively represent different metal chalcogenides, and the metal chalcogenide is doped with any one or a combination of at least two of oxygen, nitrogen, or chlorine.
2. The CdTe thin film cell having multiple window layers of a tandem composite structure according to claim 1, wherein, The content of the doping element in the metal chalcogenide is ≤32wt%.
3. The CdTe thin film cell having multiple window layers of a tandem compound structure according to claim 1 or 2, wherein, The thickness of a single layer of the window layer is 10-50nm; And / or, the total thickness of the window layer is 10-500nm.
4. A method of fabricating a CdTe thin film cell having a multi-layered, tandem, composite window layer as claimed in any one of claims 1 to 3, characterized in that, The preparation method comprises the following steps: (1) sequentially depositing a transparent conductive layer and a buffer layer on the surface of a glass substrate; (2) depositing a window layer of a multi-layer cyclic composite structure on the surface of the buffer layer; (3) sequentially depositing an absorption layer, a back contact layer, and a metal electrode layer on the surface of the window layer, and obtaining a CdTe thin-film cell with a window layer of a multi-layer cyclic composite structure after annealing treatment.
5. The preparation method according to claim 4, characterized in that, The glass substrate in step (1) comprises soda-lime glass; And / or, the deposition method of the transparent conductive layer and the buffer layer in step (1) comprises chemical vapor deposition, respectively; And / or, the material of the transparent conductive layer in step (1) comprises fluorine-doped tin oxide; And / or, the material of the buffer layer in step (1) comprises any one of tin oxide, zinc tin oxide, or cadmium tin oxide.
6. The preparation method according to claim 4, characterized in that, The deposition method of the window layer in step (2) comprises magnetron sputtering; The gas atmosphere of the magnetron sputtering method is argon, or a combination of argon and a doping gas, and the doping gas comprises any one or a combination of at least two of oxygen, nitrogen, and chlorine; And / or, the vacuum degree of the magnetron sputtering method is 1-10 mTorr, and the power density is 0.1-5 W / cm 2 .
7. The preparation method according to claim 4, characterized in that, The deposition method of the absorption layer in step (3) comprises near-space sublimation, and the deposition temperature is 400-800℃; And / or, the deposition method of the back contact layer and the metal electrode layer in step (3) comprises magnetron sputtering, respectively; And / or, the material of the absorption layer in step (3) comprises cadmium telluride, and the thickness is 2-6μm; And / or, the material of the back contact layer in step (3) comprises copper-doped zinc telluride; And / or, the material of the metal electrode layer in step (3) comprises molybdenum.
8. The preparation method according to claim 4, characterized in that, The annealing temperature in step (3) is 100-300℃; And / or, the annealing time in step (3) is 1-60min.
Citation Information
Patent Citations
Cadmium telluride thin-film solar cell and preparation method thereof
CN111341859A